Signaling Responses to N Starvation: Focusing on Wheat and Filling the Putative Gaps With Findings Obtained in Other Plants. A Review - Kong, Lingan; Zhang, Yunxiu; Du, Wanying; Xia, Haiyong; Fan, Shoujin; Zhang, Bin (Frontiers in Plant Science, 2021)
Wheat is one of most important food crops worldwide. In the past decades, increasing fertilizers, especially nitrogen (N), has been used to maximize wheat productivity. However, a large proportion of the N is not used by plants, being lost into the environments and causing serious environmental pollution. Therefore, to achieve a low N optimum via efficient physiological and biochemical processes in wheat grown in low-N conditions is pivotal important for agricultural sustainability. Despite N stress-related research on wheat captures an exciting field, how this plant adapts and responds to N starvation is far from being understood. This review summarizes the current knowledge on the signaling mechanisms in wheat plants responding to N starvation. Further, we conceivably fill the putative gaps with knowledge from other plants, mainly including Arabidopsis, maize and rice. The development of optimized root system architecture (RSA), improved N acquisition and assimilation as well as fine-tuned autophagy is as strategies to respond to N starvation. As secondary messengers and signal molecules, calcium, nitric oxide, reactive oxygen species and phytohormones play essential roles in sensing environmental N starvation and tranducing this signal into an adjustment of N transporters and phenotypic adaptation. The multifaceted functions of miRNAs, transcript factors and protein reversible phosphorylation in regulating the expression of their target genes (proteins) for low-N tolerance are also summarized. We tried to construct regulatory networks in RSA modification, N uptake, transport, assimilation and remobilization using these modules.